Factors Affecting Financial Performance Of District/City Local Government Of Yogyakarta - Aristyan Jeffri Nugroho; Martianus Budiantara (Universitas Mercu Buana Yogyakarta, 2016)
The research aims to find out factors of financial performance of local goverment regencies or city in Yogyakarta. Independent variabel are wealth of local goverment, dependence with central goverment, and local goverment expenditures. On the other hand the dependent variable is financial performance of local goverment as measured by the efficiency ratio. Population of this research are local goverment financial report (LKPD) of Yogyakarta period 2010-2014 audited by BPK. The sample are estimate realization report (LRA) all regencies or city and the province of Daerah Istimewa Yogyakarta. Hypothesis of this research were examined by using multiple regression in SPSS 16 software. Result of this reearch indicate that wealth of local goverment have significant positive effect on the financial performance of local goverment. Dependence with central goverment have significant positive effect on the financial performance of local goverment. Then, local goverment expenditures also have significant positive effect on the financial performance of local goverment. Faktor-faktor yang mempengaruhi kinerja keuangan pemerintah daerah kabupaten/kota yogyakarta